(untitled) (ACTA MEDICA PERUANA, 2022)
Hemorrhagic cholecystitis is a rare complication of acute cholecystitis, but with high mortality. Clinically it is identical to acute cholecystitis, and it does not usually present with gastrointestinal bleeding. We present the case of a 57-year-old man, with no history or use of anticoagulants, referred to our hospital for a "gallbladder tumor", after tomographic and cholangioresonance studies, associated with a drop in serum hemoglobin, suspicion of him is defined. He enters the operating room and a gangrenous gallbladder is evident, containing clots and stones. Confirming his diagnosis with histopathological study. Due to its clinical similarity, it should be considered in patients with a history of anticoagulant therapy, trauma, malignancy, or findings consistent with acalculous cholecystitis. But it can occur in patients with no history and be associated with cholelithiasis. Early diagnosis of this potentially fatal complication is important to facilitate urgent surgical management, imaging support being necessary for its suspicion.